PENINGKATAN KADAR HEMOGLOBIN MELALUI PEMBERIAN REBUSAN DAUN KELOR PADA REMAJA PUTRI UNTUK MENCEGAH ANEMIA DI SMA N 4 BINJAI - Arshanta Anastasia Naibaho; Hizkianta Sembiring (Universitas Murni Teguh, 2026)
Anemia is a condition in which hemoglobin (Hb), hematocrit, and red blood cell counts are below normal levels or the recommended limits. Various pharmacological and non-pharmacological approaches have been implemented to address anemia in adolescents. One such approach is the use of moringa leaves, which are commonly found in North Sumatra. This study aims to determine the effect of moringa leaf decoction on increasing hemoglobin levels in adolescent girls at SMA N 4 BINJAI. This study used a quantitative approach. The analytical pre-experimental research design used a one-group pre-post-test design. Twelve respondents were selected using a purposive sampling technique. Data analysis was performed using a Paired Samples T-Test. The results of this study using the Paired Samples T-Test showed a p-value of 0.001 (p < 0.05), indicating a significant difference between hemoglobin levels before and after the intervention. This indicates a significant effect of Moringa leaf decoction on increasing hemoglobin levels to prevent anemia in adolescent girls. It is concluded that Moringa leaf decoction increases hemoglobin levels in adolescent girls to prevent anemia and can be applied as a non-pharmacological therapy in the management of hypertension in health facilities.